2000
DOI: 10.1007/s004019900168
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-synuclein-immunoreactive cortical Lewy bodies are associated with cognitive impairment in Parkinson's disease

Abstract: Amygdala, hippocampus and six cortical gyri were examined for the Lewy body (LB) degeneration and Alzheimer's disease (AD) type changes in 45 patients with Parkinson's disease (PD). For detection of LBs, the brain areas were stained with an antibody against alpha-synuclein. The extent of neuropathological lesions was investigated in relation to cognitive dysfunction and apolipoprotein E (apoE) epsilon4 allele dosage. At least one cortical LB was found in 95% of cases (43/45). Furthermore, 40% of cases (18/45) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
200
2
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 312 publications
(219 citation statements)
references
References 31 publications
14
200
2
3
Order By: Relevance
“…This notion is supported by studies showing that the density of ␣-syn pathological inclusions correlates with disease severity in demented PD and DLB patients (62)(63)(64)(65)(66). Moreover, transgenic mouse models suggest that ␣-syn inclusions impair cellular function by obstructing normal cellular trafficking and disrupting cell morphology (44,67).…”
Section: E46k Mutation In ␣-Synuclein Increases Amyloid Formationmentioning
confidence: 84%
“…This notion is supported by studies showing that the density of ␣-syn pathological inclusions correlates with disease severity in demented PD and DLB patients (62)(63)(64)(65)(66). Moreover, transgenic mouse models suggest that ␣-syn inclusions impair cellular function by obstructing normal cellular trafficking and disrupting cell morphology (44,67).…”
Section: E46k Mutation In ␣-Synuclein Increases Amyloid Formationmentioning
confidence: 84%
“…Many PD patients have substantial load of Alzheimer's histopathological features [15,17,48,49]. There is evidence that dementia in PD is associated more closely with cortical deposition of the hallmark component of Lewy bodies, α-synuclein, than with Alzheimer's pathology [2,43,68], although this conclusion is disputed by some authors [82]. A strong correlation between frequency of plaques and neurofibrillary tangles with neocortical Lewy bodies has been reported [4], suggesting common origin and/or cooperativity between the two types of pathology.…”
Section: Introductionmentioning
confidence: 99%
“…However, molecular pathological alterations are also linked with the incidence of cognitive deficiency in PD. Mattila et al has documented a study, where α-synuclein aggregation and Lewy body formations were reported to be highly correlated with cognitive impairment in PD [37].…”
Section: Reviewmentioning
confidence: 95%